Environmental protection under national legislation and agreements between oil and gas multinational corporations and host communities - Adedipe, F. (Canterbury Christ Church University, 2023)
The exploration, production and shipment of crude oil and gas by multinational corporations (MNCs), involved in bilateral treaties in Nigeria has perpetrated environmental disasters upon host communities. This has been as a result of oil and gas leaks from MNCs facility into the air, land, water, marine habitat, and cultural life of host communities are heavily polluted. International law has attempted to regulate the activities of MNCs particularly in the protection of the environment in which they operate through four main treaties: Universal Declaration of Human Rights,1International Covenant on Economic, Social and Cultural Rights (ICESCR), 2 Declaration of the United Nations Conference on the Human Environment (Stockholm Declaration)3and Declaration of the United Nations on Environment and Development (Rio Declaration). In addition, the demand for environmental protection is foregrounded under the right to life recognized in article 6 of the International Covenant on Civil and Political Rights (ICCPR). However, a major criticism of international law is its inapplicability to non-State actors such as corporations. This creates a lacuna in the legal framework of protections which has been exploited by opportunistic MNC’s. International soft law such as the Global Compact, Organization of Economic Cooperation and Development (OECD) Guidelines for Multinational Enterprises and United Nations Guiding Principles (UNGPs) on Business and Human Rights encourages corporations to respect environmental rights and creates substantive standards for States to hold corporations accountable for environmental and human rights violations. The challenge remains that these international laws having soft law status are not binding on corporations. Also, a further problem is that several developing state governments may be complicit in the environmental abuses perpetrated by MNCs for the purpose of boosting economic development. Therefore, this research proposes the regulation of MNCs under national legislation and bilateral investment treaties. It recommends certain preventive and mitigation measures against the adverse environmental effect of their activities in the exploration of natural resources, waste disposal and other connected operations in developing communities in Nigeria. Some of these preventive measures include environmental impact assessment (EIA), mandatory reporting and disclosures, community stakeholder participation, environmental management and safety practices, with activity, temporal and spatial management as mitigation measures. Also, clean-up and compensation by MNCs are effective remedies for environmental abuses. Furthermore, fines, blacklisting, withdrawal of license and criminal charges are recommended for the enforcement of environmental protection of host communities.
Permalink: https://repository.canterbury.ac.uk/item/95yw5/environmental-protection-under-national-legislation-and-agreements-between-oil-and-gas-multinational-corporations-and-host-communities
Keywords: Agreement; Environment (protection); Host communities; Multinational corporations; Oil and Gas Industry

Sustainable biofuel regulation and production in the SADC region : a comparative analysis - Kandala, Lupwana Jean Jacques (University of Johannesburg, 2017)
Keywords: Biofuel; Biomass energy; SADC

Joint Development of Offshore Polar Oil and Gas Resources and the United Nations Convention on the Law of the Sea - Abrahamson, John (Australian National University, 2015)
This thesis examines whether the establishment of Joint Development Zones (JDZs) for the development of offshore oil and gas resources in the Arctic and Southern Oceans can effectively resolve competing continental shelf and outer continental shelf (OCS) claims arising under the provisions of Article 76 of the United Nations Convention on the Law of the Sea (LOSC). One of the effects of global warming has been increased interest in oil and gas activity in the Arctic region, however there is significant concern as to the related environmental risks. The Environmental Protocol to the Antarctic Treaty currently suspends exploration for state parties for oil and gas in the Southern Ocean, however current exploration has been reported. A JDZ may be defined as an inter-governmental arrangement of a provisional or permanent nature, designed for joint exploration and exploitation of the hydrocarbon resources of the sea-bed. JDZs are generally based on agreements to suspend sovereignty claims and share offshore oil and gas in the JDZ region. The thesis was prepared to contribute to the prevention of potential international conflicts over offshore oil and gas resources. State claims may be based on historic claims, interpretation of treaties, and LOSC exclusive economic zone (EEZ), continental shelf, and OCS delimitation provisions. LOSC provides dispute resolution alternatives, including referral to the International Court of Justice and international arbitration. A significant number of states have, however, preferred to adopt JDZ agreements. The methods used for the thesis included analysis of LOSC maritime delimitation provisions, existing JDZ agreements, the terms of model JDZ agreements, and analysis of current Arctic and Southern ocean maritime boundary disputes. The principal thesis conclusions are: - JDZs can resolve resource disputes as demonstrated by the existing international state practice in adopting JDZs. JDZ regimes are not a universal panacea, however, and successful JDZs are based on the continued political support of the respective states; - LOSC maritime boundary delimitation provisions may not resolve boundary disputes, which can arise due to issues including conflicting sovereignty of land territory; - Specific Arctic and Southern Ocean disputed regions have similar characteristics to existing JDZs. JDZs may therefore potentially apply to resolve these disputes; - JDZs can potentially provide solutions for disputed boundaries, such as between United States/Canada (Beaufort Sea), United States/Russia (Bering Sea) in the Arctic Ocean region, and between United Kingdom/Argentina/Chile in the Southern Ocean; - JDZ should be adapted to better protect and preserve the marine environment, and to provide a significant liability regime similar to the Greenland regime; - JDZs should support a framework of regional governance, including Arctic Council or Antarctic Treaty representation in the respective JDZs; and - Potential game changing events may affect the use of JDZs in the future, including political and technological developments, and significant oil and gas discoveries. The result of the thesis conclusions is to prove the hypothesis that JDZs can effectively resolve resource conflicts in the Arctic and Southern Ocean regions.

Nuclear energy in Africa : a legal framework for sustainable energy access - Barnard, Michelle (North-West University, 2014)
The promotion of sustainable development is an objective shared by African Union (AU) member states and the pursuance thereof is expressly mandated by the Constitutive Act of the African Union, 2000 and the Treaty Establishing the African Economic Community, 1992. Lack of access to modern energy sources, such as electricity and the heavy reliance on traditional biomass as primary energy source are factors contributing to the non-achievement of the promotion of sustainable development. These factors are collectively referred to as energy poverty. The African Continent as a whole has limited, and in some instances, lack access to modern energy sources while the majority of its population relies heavily on traditional biomass as primary energy source. Africa can accordingly be classified as an energy poor region–a situation which does not bode well for the promotion of sustainable development. Access to reliable, affordable, economically viable, socially acceptable and environmentally sound energy services and resources is fundamental to socio-economic development. Mitigating the impacts of energy poverty and more specifically lack of access to modern energy sources on the sustainable development of Africa depends upon ensuring increased access to modern energy sources. The above-mentioned instruments furthermore contain provisions which link regional cooperation on the formulation of coordinated regional law and policy on areas/matters of common concern with the achievement of the objective of promoting sustainable development in Africa. One of the areas of common concerns listed is that of energy. Regional cooperation must accordingly be geared towards the effective development of the continent‘s energy and natural resources; promoting the development of new and renewable energy in the framework of the policy of diversification of sources of energy; and establishing an adequate mechanism of concerted action and coordination for the collective solution of the energy development problems within the AU. The formulation of coordinated energy law and policy should take place with reference to the specific sources of energy to be regulated. In this regard, the provisions of the Abuja Treaty and other sub-regional energy access initiatives list various sources of energy as forming part of a diversified AU energy mix – one of which is nuclear energy. In this study recommendations are made as to what should be embodied in a coordinated AU regional nuclear legal framework aimed at regulating increased access to nuclear energy capable of contributing towards the promotion of sustainable development. The recommendations are based on an examination of relevant international, regional and sub-regional legal instruments and other initiatives.
Keywords: African Union; Coordinated legal framework; Energy access; Energy poverty; Nuclear energy; Regional cooperation; Sustainable development

Regulating trade in petroleum under the WTO Regime: trade rules vs. reality of the petroleum industry - Bitenov, Gani (McGill University, 2014)
This thesis critically assesses the effectiveness of WTO legal rules in the regulation of international trade in petroleum and highlights potential conflicts between competing resources of energy from the WTO regime’s perspective. The theoretical framework of the thesis is built on the concepts used in natural resource economics, trade theories and international relations. On the basis of Hotelling’s rule of natural resource economics, it proposes a model that reconciles the use of petroleum and the development of renewable sources of energy in the power generation sector, which prospectively can be adopted with respect to the transport sector and other sectors involving energy use. The proposed model may improve global sustainable development. However, it is argued that WTO rules are not properly designed to regulate trade in petroleum and, if applied without due respect to specific issues pertaining to the petroleum industry, would obstruct the achievement of the social optimum, and detrimentally affect the national economies of WTO members and global welfare in general. To improve the WTO system, I propose a reformation of its normative ideology through the introduction of the strategic trade policy theory in complement to the neoclassical theory of trade, at least when trade in energy is concerned. On the basis of the study of the applicability of WTO rules to trade in petroleum and a review of proposals put forward by other scholars to improve the regulation of trade in energy, it is argued that the most effective way to improve the trading regime is to negotiate a new general agreement on trade in energy.The role of the WTO in the regulation of trade in energy is analyzed through a regime management theory borrowed from international relations studies. It is argued that the WTO as a regime manager is capable of improving the regime by properly maintaining the existing equilibrium and by initiating, and leading in negotiations of a new equilibrium.
https://escholarship.mcgill.ca/concern/theses/ws859j68h
Keywords: Petroleum industry and trade; Trade regulation; WTO trade rules

Nigeria, oil and gas exploration and the Niger delta question : a study in corporate social responsibility - Bribena, E. K. (North-West University, 2011)
This thesis addresses issues of the Niger Delta question which represents one of the most intractable sources of socio-political destabilization in the Niger Delta region of Nigeria. The study is on the intricate dynamics amongst the Nigerian state, the transnational oi l corporations, the oil producing communities and the insurgent militia conflict. It investigates and explicates the "paradox of plenty" and the "resource curse", the "absentee government" and "state capture" and the debilitating effects of petroleum politics in Nigeria. The economic exploitation of the Niger Delta region's vast crude oil reserves by transnational oil corporations and government authorities is juxtaposed with the spectre of environmental degradation, human rights violations, and the recurrent rule of impunity. The protracted problems of the Niger Delta region thus, provide us with a pertinent analytical and contextual framework for the study of the dynamics and issues of transparency in other African petro-dollar states. It is argued in this study that the Niger Delta crisis is a conflict of values and fight for resources arising from decades of unacceptable standards of oil exploration and the absentee character of the Nigerian State. By its very nature, the study called for a qualitative approach, supplemented by unstructured interviews using aide memoirs with selected officials, on the basis of their innate knowledge of the subject matter. The legal comparative research method, with a historic component also played an integral role in this study. Some key findings and conclusions: 1. The study found that the Niger Delta crisis graduated from mère political agitations for state creation and provision of social amenities to extreme acts of hostage-taking and a twist of violence as a result of treating a major problem affecting the development of the Niger Delta people with levity for too long a period. 2. The study found that the on-going crisis in the Niger Delta region of Nigeria is a conflict of values and fight for resources amongst the oil-bearing people of the Niger Delta, transnational oil corporations and the Nigerian Government. 3. The study established some causal nexus between oil and poverty; oil and corruption; and, oil and human rights abuses. 4. That, the Niger Delta crude oil conflict is essentially a manifestation of state capture and inertia on the part of the Nigerian Government. 5. The study found that the Niger Delta economies are "criminalized" and are often characterized by conditions of anarchy and impunity. And this disorder is embedded in the dynamics of resource extraction, the nature and role of "shadow" state actors, as well as the interplay and patterns of relationships between organized criminal syndicates and the transnational oil corporations in the host communities. The study recommends, inter alia: I. That steps be taken by government to re-define its philosophy of national economic development from a state-driven to citizens-driven philosophy. To this end, Nigeria must seek to develop by developing its citizens, the aggregate of whose satisfactory living conditions should form the criteria for measuring national development. II . That effort must be made to steer the nation towards proper fiscal federalism. The present "food is ready" economy whereby federating units are enslaved to national "cake sharing" instead of value generation, discourages entrepreneurship and sustainable development. It promotes undue dependency on petroleum products, inequity and ethnic distrust. Ill. That Nigeria needs productive resource control, not just development in the sense of house and bridge building. What is needed is a noticeable leap in the standard of living in the Niger Delta. Thus, people and not federal accounts must be the object of improvement. IV. It is recommended that government should ensure robust, independent and co-ordinated oversight of the oil industry including its impact on human rights. V. Transnational oil corporations should undertake full corporate social responsibility and comprehensive assessment of the social and human rights impacts of all oil and gas projects, ensuring that adequate information is provided to affected individuals and communities and that the process is transparent. VI. It is strongly recommended that an Oil Pollution Liability Trust Fund should be established by the Federal Government in concert with oil companies. The fund will be made up of a percentage of tax levied on oil companies and a percentage of earnings of the Federal Government from oil. The fund should be used in ameliorating the conditions of the impacted environment and people. It is hoped that these findings and recommendations will go a long way in the quest for significant environmental and social improvements in the Niger Delta region of Nigeria.
Keywords: CSR; Corporate Social Responsibility; Nigeria; Petroleum industry and trade